Awareness of the use of standard precautions during care of people living with HIV by ward attendants in Indian hospitals - Ryan Fernandez; Tony D S. Raj; Elsa Heylen; Laura Nyblade; Dhinagaran Devadass; Krishnamachari Srinivasan; Maria L Ekstrand (Wolters Kluwer Medknow Publications, 2022)
Context: Standard precautions (SP) are infection prevention practices universally used during patient care to lower infection transmission. Aims: The aim of the study was to (1) assess Indian ward attendants' (WAs) knowledge, perceived efficacy, and self-efficacy regarding SP and (2) examine correlates of SP self-efficacy and intent to use unnecessary precautions during care of people living with HIV. Subjects and Methods: Data are sourced from a face-to-face baseline survey of a stigma-reduction trial among 1859 WAs from Indian hospitals. Percentages were used to describe categorical variables means and standard deviations for continuous variables. Multiple regressions examined associations between measures. Results: WAs who had heard of SP had 44% higher odds of confidently using SP than those who had not heard of them. Those aware of universal SP use were 43% more likely to feel confident in using SP but also reported greater intent to use unnecessary precautions. Conclusions: Hospitals could implement SP training for WAs, as their knowledge of universal use was lacking.